1985
DOI: 10.1111/j.1471-0528.1985.tb01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Domperidone; secretion in breast milk and effect on puerperal prolactin levels

Abstract: The possible effect on the infant of dopamine antagonists used to promote lactation is cause for concern. Domperidone (Motilium) may be safer than other drugs in this group as it does not cross the blood-brain barrier. The mean serum level of prolactin 2 h after treatment with 20 mg of domperidone in the puerperium was 255 ng/ml compared with 150 ng/ml after a placebo. The mean domperidone level in all breast milk samples during treatment with IOmg, three times daily, was 2.6 ng/ml. This was significantly more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 14 publications
2
29
0
1
Order By: Relevance
“…Separate studies with intramuscular or oral domperidone indicated that the drug had the same potency as metoclopramide in inducing prolactin release. [102][103][104] Based on these findings, it is unlikely that the different prolactin levels caused by the various antagonists are due to different affinities at the dopamine D 2 receptor, as domperidone and clebopride have comparable affinities (see Table 1) 1 . It is also unlikely that the various antagonists can differently modulate the release of dopamine from the tuberoinfundibular pathway, as dopamine D 2 autoreceptors are absent in this pathway.…”
Section: Hyperprolactinaemiamentioning
confidence: 98%
“…Separate studies with intramuscular or oral domperidone indicated that the drug had the same potency as metoclopramide in inducing prolactin release. [102][103][104] Based on these findings, it is unlikely that the different prolactin levels caused by the various antagonists are due to different affinities at the dopamine D 2 receptor, as domperidone and clebopride have comparable affinities (see Table 1) 1 . It is also unlikely that the various antagonists can differently modulate the release of dopamine from the tuberoinfundibular pathway, as dopamine D 2 autoreceptors are absent in this pathway.…”
Section: Hyperprolactinaemiamentioning
confidence: 98%
“…In another study the same authors found that the concentrations in serum and in milk to be 8.0 and 0.24 ng/ml, respectively, with an M/P ratio of 0.03, 2 h after the administration of a single dose of 20 mg of domperidone. At 4 h post-dose the M/P ratio was 1.1 (32). After 5 days of treatment with domperidone (10 mg 3 times a day) Da Silva et al found an average serum and milk concentrations of 6.6 and 1.2 ng/ml respectively, with an M/P ratio of 0.18.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…No of side effects has been reported in the infants whose mothers take domperidone (31,32,40,41). Mothers with cardiac diseases should avoid using this drug due to potential arrythmia (43).…”
Section: Side Effects For Mother and For Infantmentioning
confidence: 99%
See 1 more Smart Citation
“…Domperidone administration is well known to induce hyperprolactinemia. This effect is attributable to domperidone blockade of pituitary dopamine D 2 receptors [24,25,[29][30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%